THE EFFECT OF THYROID DISEASES ON THE CARDIOVASCULAR SYSTEM - Shagazatova B. X.; Zakirova F. Sh.; Axmedova F. Sh. (Modern American Journals, 2025)
Thyroid diseases, especially hypothyroidism, are widespread among the population and occur clinically in subclinical or manifest forms. Hypothyroidism results from a decrease in thyroid hormone secretion or a decrease in receptor sensitivity in target organs. It is known that thyroid hormone receptors are present in almost all tissues of the body, including the myocardium of the heart and the endothelium of blood vessels. Therefore, many patients with thyroid diseases are at high risk of developing cardiovascular pathologies. There are different scientific opinions on the effect of treating hypothyroidism with hormone replacement therapy on the cardiovascular system, and this issue still has no clear solution and remains relevant.
Keywords: hypothyroidism, atherosclerosis, arterial hypertension, heart failure, Type B sodium uretic peptide NT-proBNP, thyroid hormones, dyslipidemia